Patterns of variations in lipid molecular profile during larval development of red king crab, Paralithodes camtschaticus, and Japanese mitten crab, Eriocheir Japonica - Ekaterina Ermolenko; Tatyana Sikorskaya; Valeria Grigorchuk; Tigran Gevorgyan; Svetlana Rodkina; Elena Bizikashvili; Sergey Maslennikov (Scientific Reports)
Abstract The red king crab, Paralithodes camtschaticus, and the Japanese mitten crab, Eriocheir japonica, are the major commercially valuable species. In addition to their high nutritional value, these crabs are used as objects of ecological research. To extend our knowledge of crustacean biochemistry and provide a more comprehensive model of lipidomic patterns during embryonic and larval development of these crab species, we studied the dynamics of molecular species profiles of reserve lipids such as triacylglycerols (TG) and membrane lipids such as glycerophospholipids (PL). A complete disappearance of TG was observed in zoea IV larvae of E. japonica and zoea III larvae of P. camtschaticus. The appearance of TG at older stages of larval development was accompanied by considerable changes in TG composition. The dynamics of PL with major polyunsaturated fatty acids (PUFA) (20:5n-3, 22:6n-3, and 20:4n-3) during the larval development was species-specific. The obtained results indicate different demands for PUFA in P. camtschaticus and E. japonica, which can be taken into account when selecting optimum diets. The lipidomic approach allows identifying new patterns of lipid changes during crab embryonic development, which may be useful for improvement of aquaculture techniques.